David Hume acerca del materialismo - Calvente, Sofía (2023)
During the 17th and 18th centuries, an intense debate concerning materialism took place. This paper aims to describe David Hume’s position within this debate. I claim that, even though Hume rejects substantialist metaphysics to focus on the study of perceptions, he defends a position concerning the relationship between mind and matter. However, this position is rather complex to reconstruct since it is not explicitly stated in the texts edited during Hume’s life. I propose to define it as a restricted materialism since, regarding the nature of mind, Hume discards both the materialist and the immaterialist positions; although concerning the causes of thought he comes close to materialist positions by using arguments based on experience and the analogy with nature.